METODE CLIMBING FORM DALAM PELAKSANAAN PEKERJAAN CORE WALL âSTUDI KASUS PROYEK HOTEL QUEST SOLOâ PT ADHI KARYA - , FARADINDA PRABANDINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The three main components that need to be planned carefully in concrete construction work, which is a mixture of concrete, concrete reinforcement, and formwork or formwork. All three of these components greatly influence the success of a job structure, including the structure of the core wall. The rebarring analysis has an important function in the power structure. Selection of construction methods will also have a significant impact assessed in terms of an effective and efficient system that is used for completion of the work structure of the core wall. Because the core structure of the wall is a large vertical concrete structures and has a typical shape that required a special system in practice, using climbing formwork system. The system uses a Tower Crane lifting equipment in the process of core wall. In the cost analysis climbing form system to work on a building wall cores obtained 23 floor price that is more efficient than a system with slip form, has a price difference of Rp Rp 115.500.000,00. For climbing form system itself worth USD 109.754.014,00 while the slip systems form Rp 225.254.014,00. Although in terms of the number of workers more 2 and more time of 0.5 days, but the excess climbing system is much more efficient in terms of cost, so that the system is widely used in construction projects.